Pengaruh Financial Performance dan Corporate Governance terhadap Pengembalian Atas Ekuitas - Khusnul Khuluqi (Universitas Pamulang, 2022)
This study aims to examine the effect of financial performance and corporate governance indicators on returns on equity in basic and chemical industrial sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This type of research is an associative quantitative research with secondary data sources obtained from the company's financial statements published by the Indonesia Stock Exchange. Determination of the sample by purposive sampling method in order to obtain 75 samples. The data analysis method used is multiple linear regression analysis, the data is processed using software eviews 12. The results of the study found that (1) financial performance proxied by debt to equity ratio (DER) had a negative and significant effect on return on equity (ROE), (2) financial performance as proxied by the Acid-test Ratio (ATR) has no significant effect on return on equity (ROE), (3) Corporate Governance as proxied by the proportion of institutional ownership (KI) has no significant effect on ROE, (4) Corporate Governance which is proxied by proxied by the proportion of managerial ownership (KM) has no effect on ROE, (5) corporate governance as proxied by the size of the board of commissioners (DKOM) has no significant effect on ROE, (6) corporate governance proxied by the proportion of independent commissioners (KIND) has no significant effect on ROE, (7) Corporate Governance which is proxied by n the audit committee (UKAD) has no significant effect on ROE.